Is low load blood flow restriction training an effective intervention in improving clinical outcomes in adults with lower extremity pathology: a systematic review. (3rd September 2019) - Mirando, Michael; Reusser, Abby; Sherer, Beth; Reinhart, Carlton; Murray, Leigh
Abstract: Background: Blood flow restriction (BFR) is a safe and effective method of muscle strengthening that involves placing a tourniquet on a limb to occlude venous blood. This reduces the amount of oxygen and produces an anaerobic environment in the muscle, thus producing hypertrophy in the muscle. Objective: The primary purpose of this systematic review was to determine whether low load BFR training impacts functional outcomes and is effective when rehabilitating patients with lower extremity pathology. Methods: Balance, gait speed/endurance, functional strength, and mobility/fall risk was assessed while self-reported outcome measures assessed general health, pain with function, and function. All studies compared low load BFR to high load resistance training. A total of 3264 articles were reviewed and five RCTs met the inclusion criteria and were included in this analysis. Results: Participants' ages ranged from 18 to 70 years old and sample sizes ranged from 17 to 69 participants. Results demonstrated significant changes from baseline in all outcomes with BFR. Conclusion: Low load BFR training can produce significant improvement in both functional and self-reported outcomes; however, it did not show that low load BFR was a better and more effective treatment when compared to high-load resistance training.